Unimprovable Integral Estimate for Solutions of the Dirichlet Problem for Quasilinear Elliptic Equations of the Second Order in a Neighborhood of an Edge - Plesha, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain an exact estimate for the second derivatives of solutions (in the weight Sobolev norm) of the Dirichlet problem for quasilinear second-order elliptic equations of nondivergence type in a neighborhood of an edge of a domain.